Methods to foster oral proficiency in English in engineering students through innovative classroom teaching - Matilda, P. Rosy; Allamneni, Sharada (International Journal of Psychosocial Rehabilitation, 2020)
India is a country where every second or every third student is an engineer but most of them are still unemployed due to various factors, oral proficiency being one of them. Traditional classroom teaching methods and outdated methodologies, owing to poor exposure result in a majority of engineers unable to fetch jobs for themselves. Exposure to the present trends and making them aware of the needs of the industry is the need of the hour. Inculcating new methods in teaching which give the students hands-on experience to deal with the interview pressure and sustain a job should be prioritized since day one of their engineering education. Eleventh hour preparations for interviews have never been beneficial. This paper aims at providing innovative classroom teaching methods to improve the oral proficiency of engineering students.